The Effectiveness of Travel Agent Contracts in Increasing The Number of Booking at The Café - International Buffet Restaurant - Ni Made Mahayuni; Ni Nyoman Triyuni; I Ketut Astawa; I Putu Budiarta (The Postgraduate School of Tourism Sahid Polytechnic, 2023)
Purpose: Travel and leisure demand reach a considerable number through tourism development. In accommodating travel and leisure needs, the solution was found by using a third party to arrange the itinerary. This is how travel agent existence could be used as a marketing strategy. This trick also done by The Café - International Buffet Restaurant. This research was conducted to analyze the implementation of travel agent contracts in increasing the number of bookings and identify the most effective travel agent contracts in advancing the number of bookings. Research methods: Regarding finding the result, this research used the quantitative technique by applying the effectiveness formula and categorizing the result with the effectiveness level. The result is performed using tables, numbers, percentages, and charts processed by Microsoft Excel. In describing the explanatory, it uses descriptive analysis, which uses quantitative techniques to interpret the meaning of the result. The results will be solved as information on the problem formulation, conclusion, and suggestion. Results and discussion: The implementation of travel agent contract Chinese market and travel agent contracts in the non-Chinese market are the objects of this research. Implication: Based on the analysis, the travel agent contract in the non-Chinese market is more effective in increasing the number of restaurant bookings regarding its contribution exceeding the target that must be achieved. Keywords: Effectiveness, travel agent contract, restaurant booking